2004
DOI: 10.1140/epja/i2003-10183-2
|View full text |Cite
|
Sign up to set email alerts
|

Form factors in the “point form” of relativistic quantum mechanics: Single- and two-particle currents

Abstract: Electromagnetic and Lorentz-scalar form factors are calculated for a bound system of two spinless particles exchanging a zero-mass scalar particle. Different approaches are considered including solutions of a Bethe-Salpeter equation, a "point form" approach to relativistic quantum mechanics and a non-relativistic one. The comparison of the Bethe-Salpeter results, which play the role of an "experiment" here, with the ones obtained in "point form" in single-particle approximation, evidences sizable discrepancies… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 37 publications
1
18
0
1
Order By: Relevance
“…At low Q 2 , it is noticed that the fast drop off of the form factor appearing in some cases has disappeared. This result supports the suggestion made elsewhere [20] that this strange behavior of the form factor was in relation with some symmetry breaking. At high Q 2 , the right power-law behavior of the charge form factor is obtained after restoring properties related to space-time translations, though it was not always so before ("P.F.").…”
Section: "Point Form"supporting
confidence: 93%
See 2 more Smart Citations
“…At low Q 2 , it is noticed that the fast drop off of the form factor appearing in some cases has disappeared. This result supports the suggestion made elsewhere [20] that this strange behavior of the form factor was in relation with some symmetry breaking. At high Q 2 , the right power-law behavior of the charge form factor is obtained after restoring properties related to space-time translations, though it was not always so before ("P.F.").…”
Section: "Point Form"supporting
confidence: 93%
“…Getting a small total mass can be achieved by increasing the attraction between constituents. While it is then expected that the system shrinks, some approaches have instead show that the charge radius was increasing and could go to ∞ while M → 0 [20]. This strange result could be the sign that some important symmetries, like those considered in this paper, are missed.…”
Section: "Point Form"mentioning
confidence: 76%
See 1 more Smart Citation
“…Within the context of a toy model calculation in Refs. [Des04,Des06], it has e.g. been shown that the neglect of two-body currents in the point form does affect the FFs in a more drastic way than their neglect in the instant or light-front forms.…”
Section: Constituent Quark Modelsmentioning
confidence: 99%
“…(12). Calculating the contribution of many-particle terms is quite tedious and this has been done for a limited number of cases with the aim of accounting for current conservation [50] or getting the expected asymptotic behavior of the charge form factors for the pion [45] or for a system of scalar constituents in the point form-approach [50]. Moreover, if these extra terms restore the equivalence of predictions of different approaches, we expect that they should occur at all orders in the interaction.…”
Section: Constraints From Poincaré Covariant Space-time Translationsmentioning
confidence: 99%